Effective combination therapy of percutaneous ethanol injection and chemotherapy based on injectable low molecular weight gels. (5th November 2018) - Li, Guotao; Liang, Yan; Sun, Changzhen; Peng, Xinyu; Hao, Na; Liu, Miaochang; Gao, Wenxia; Wu, Huayue; He, Bin
Abstract: Percutaneous ethanol injection (PEI) therapy was used in liver cancer treatment, however, the therapeutic ethanol in PEI easily flew away from injected solid tumours and hinder the treatment effect. In this paper, injectable supramolecular gels formed by self-assembly of low molecular weight gelators (LMWGs) based on glycylglycine modified phenylboronic acid were prepared to localize ethanol and load chemotherapeutic drug for in situ synergistic therapy. The mechanism, morphology and rheological property of supramolecular gels were characterized by NMR, UV, SEM, etc. The rheological study revealed that the gels were formed in situ rapidly and recovered promptly once damaged. The gels were non-toxicity to both normal 3T3 fibroblasts cells and 4T1 breast cancer cells. Doxorubicin (DOX) hydrochloride and ethanol were encapsulated in the gels for the combination of chemotherapy and PEI therapy. The in vivo anticancer activity of the DOX-loaded gels was carried out in tumour bearing mice. The injected gels were coated around tumour tissues to lock ethanol, and DOX was released sustainingly from the gels to maintain effective concentration to induce the apoptosis of tumour cells. DOX-loaded gels and the ethanol exhibited excellent therapeutic efficacy and low side effects in local cancer therapy.